Selecting Primers for RAPD, Microsatellite and Mitochondrial Cytochrome Oxidase Subunit 1 for Genetic Variation Analysis of Asian Corn Borer (Ostrinia furnacalis Guenée) Population in Java, Indonesia - Ahmad Taufiq Arminudin; Y. Andi Trisyono; Arman Wijonarko; Suputa Suputa (Jurnal Perlindungan Tanaman Indonesia, 2019)
Primer plays an important role in studying genetic diversity of an insect species. This research was aimed to select the suitable primers to visualize the genetic diversity of Asian corn borer (Ostrinia furnacalis) using Random Amplified Polymorphic DNA (RAPD), microsatellite, and mitochondrial cytochrome oxidase subunit 1 gene (mtCO1). Twenty four RAPD primers (OPA1, OPA4, OPA7,OPA8, OPA10, OPA11, OPA12, OPA13, OPB7, OPB10, OPB11, OPB12, OPB15, OPC4, OPC5, OPC14, OPC16, OPC18, OPC20, OPD3, OPD8, OPD10, OPD13, OPD14) and five microsatellite primers (T3, T4, T5, T81, D25) resulted high polymorphic informations of the genetics of O. furnacalis in Java Indonesia. Universal primers, Lep and Heb were appropriateto do molecular identification of O. furnacalis based on BLAST system on GenBank and BOLD systems.